The mechanism of building competitiveness through strategic partnering = Mechanizm budowy konkurencyjności przedsiębiorstw poprzez partnerstwo strategiczne - Adamik, Anna (Zielona Góra: Faculty of Economics and Management Press)
The paper assumes that strategic partnering, as one of the more mature forms of inter-organisational cooperation, is also an effective method of support for strategic activities of enterprises. In the light of the above, the use of strategic partnering in processes aimed at enhancing their competitiveness was proposed. The aim of the analyses is to identify and systematic the key actions in the mechanism of building competitiveness through strategic partnering of enterprises. For its implementation, a review of literature in the field of theory of organisation, theory of cooperation and partnering as well as theory of competitiveness was carried out.
Keywords: konkurencyjność przedsiębiorstw; partnerstwo strategiczne; perspektywy partnerstwa; budowanie konkurencyjności; competitiveness of enterprises; strategic partnering; perspectives of strategic; building competitiveness